Gotham City Sirens division - Calloway, Peter 1982- (DC Comics, 2012)
"Together, Catwoman, Harley Quinn and Poison Ivy are three of Gotham City's most powerful quasi-reformed criminals. But when Harley stages a riot in Arkham to reach her former employer and lover the Joker, it could be the beginning of the end for the Gotham City Sirens. As the situation inside Arkham quickly spins out of control, and Harley becomes more and more mired in her obsession with the Clown Prince of Crime, Poison Ivy and Catwoman struggle over how to handle their estranged teammate. The gotham City Sirens are ready to make their final stand, but will they be fighting each other?" -- p. [4] of cover.